Dynamic Correlations between Intrinsic Connectivity and Extrinsic Connectivity of the Auditory Cortex in Humans - Cui, Zhuang; Wang, Qian; Gao, Yayue; Wang, Jing; Wang, Mengyang; Teng, Pengfei; Guan, Yuguang; Zhou, Jian; Li, Tianfu; Luan, Guoming; Li, Liang (Frontiers in Human Neuroscience, 2017)
The arrival of sound signals in the auditory cortex (AC) triggers both local and inter-regional signal propagations over time up to hundreds of milliseconds and builds up both intrinsic functional connectivity (iFC) and extrinsic functional connectivity (eFC) of the AC. However, interactions between iFC and eFC are largely unknown. Using intracranial stereo-electroencephalographic (sEEG) recordings in people with drug-refractory epilepsy, this study mainly investigated the temporal dynamics of the relationship between iFC and eFC of the AC. The results showed that a Gaussian wideband-noise burst markedly elicited potentials in both the AC and numerous higher-order cortical regions outside the AC (non-auditory cortices). Granger causality analyses revealed that in the earlier time window, iFC of the AC was positively correlated with both eFC from the AC to the inferior temporal gyrus and that to the inferior parietal lobule. While in later periods, the iFC of the AC was positively correlated with eFC from the precentral gyrus to the AC and that from the insula to the AC. In conclusion, dual-directional interactions occur between iFC and eFC of the AC at different time windows following the sound stimulation and may form the foundation underlying various central auditory processes, including auditory sensory memory, object formation, as well as integrations between sensory, perceptual, attentional, motor, emotional, and executive processes.